2004
DOI: 10.1080/0954025032000170345
|View full text |Cite
|
Sign up to set email alerts
|

‘If they don't recognize it, you've got to deal with it yourself’: gender, young caring and educational support

Abstract: This articles discusses some of the findings of a small-scale, localized, qualitative study involving children and young people identified and processed as young carers, that are providing 'substantial care' for an adult while in primary and/or secondary school. It explores their views on managing to 'care more' whilst at school and the role that teachers and schools do and could play in supporting them. The voices of young carers suggest that educational support should be available 'as soon as' children becom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 4 publications
1
41
0
Order By: Relevance
“…This power imbalance also meant that, in relation to the outside world, where power was possessed by education, health and social care professionals, young people felt threatened, invalidated and silenced in their role (Cree 2003, Eley 2004, Robson 2004, Martin 2006, Bolas et al 2007, Earley et al 2007, Moore and McArthur 2007.…”
Section: Becoming a Caring Personmentioning
confidence: 95%
See 3 more Smart Citations
“…This power imbalance also meant that, in relation to the outside world, where power was possessed by education, health and social care professionals, young people felt threatened, invalidated and silenced in their role (Cree 2003, Eley 2004, Robson 2004, Martin 2006, Bolas et al 2007, Earley et al 2007, Moore and McArthur 2007.…”
Section: Becoming a Caring Personmentioning
confidence: 95%
“…Young carers in Moore and McArthur's (2007) Moreover, young carers did not feel that their friends could understand why they were unable to go out and socialise (Banks, Cogan, et al 2002, Cree 2003, leaving them with a sense of being 'different' as well as 'invisible'. Moreover, seven of the studies reported how the practicalities of caring were a barrier to children's socialising (Bilsborrow 1993, Gates and Lackey 1998, Eley 2004, Bolas et al 2007, Earley et al 2007, Moore and McArthur 2007. Young carers described their struggle to strike a balance between caring, schoolwork and a social life.…”
Section: Becoming a Caring Personmentioning
confidence: 96%
See 2 more Smart Citations
“…12 By using contemporary psychological and sociological studies such as the work of John and Elizabeth newson, on parenting, and Patricia Sikes, on teachers' experiences of parenthood, I will also be able to consider how these experiences were framed by women at the time. 13 Finally, as this summary indicates, I will be drawing to some extent on a case study of oxfordshire and the City of oxford, two local education authorities historically known for their progressive practice.…”
Section: Introductionmentioning
confidence: 99%